Attitude’s Framing of Political Figures in Social Media during the Pre-Election Campaign 2024 - Yuani Asilady; Siti Drivoka Sulistyaningrum; Samsi Setiadi (SAINTIS Publishing, 2025)
This research evaluates the attitudes framing of political figures in social media during the pre-election campaign 2024 by using an appraisal system analysis approach in Systemic Functional Linguistics (SFL). The main objective of this research is to examine how the three-candidates, Anies Baswedan, Prabowo Subianto, and Ganjar Pranowo, framed their political image through social media (Twitter). The data were obtained from the posts of each candidate in the period 1-13 February 2024 and analyzed using a qualitative-descriptive method with the UAM CorpusTool. The results showed that each candidate has a different communication strategy in shaping their political image. Anies Baswedan accentuates the aspects of sincerity and honesty. Prabowo Subianto presents himself as a hardworking and reliable figure. Meanwhile, Ganjar Pranowo emphasized ethical values and morality. This research confirms that social media is an important tool in building candidates' political image through language selection and framing. The findings contribute to the study of political communication and political campaign strategies in the digital era.